2017
DOI: 10.1002/anie.201700530
|View full text |Cite
|
Sign up to set email alerts
|

Taming Silicon Congeners of CO and CO2: Synthesis of Monomeric SiII and SiIV Chalcogenide Complexes

Abstract: The synthesis of the unprecedented monomeric Si selenide complex (bis-NHC)Si=Se→GaCl 2 (bis-NHC=bis-N heterocyclic carbene, H C[{NC(H)=C(H)N(Dipp)}C:] , Dipp=2,6-iPr C H ), bearing the elusive SiSe ligand as a heavy CO homologue by the reaction of the silylone-GaCl adduct (bis-NHC)Si→GaCl 1 with elemental selenium in acetonitrile, is reported. The similar conversion of 1 with excess selenium conducted in THF afforded the SiSe complex (bis-NHC)Si(=Se)Se→GaCl 3. Remarkably, the reaction of 1 with Te=P(nBu) as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 26 publications
(21 reference statements)
1
35
0
1
Order By: Relevance
“…The synthesis of the unprecedented momomeric bis(NHC)Si(Se)Se→GaCl 3 complex 35 was accomplished by the reaction of silylone→GaCl 3 adduct 31 with elemental selenium in THF (Scheme ) . The 29 Si{ 1 H} NMR spectrum of 35 displays a signal δ =−69.9 ppm, which is upfield shifted compared to the solid state CP/MAS 29 Si{ 1 H} NMR chemical shift of bis(NHC)Si(S)S→GaCl 3 complex 34 ( δ =−40.0 ppm) .…”
Section: The Reactivity Of Tetrylonesmentioning
confidence: 99%
See 2 more Smart Citations
“…The synthesis of the unprecedented momomeric bis(NHC)Si(Se)Se→GaCl 3 complex 35 was accomplished by the reaction of silylone→GaCl 3 adduct 31 with elemental selenium in THF (Scheme ) . The 29 Si{ 1 H} NMR spectrum of 35 displays a signal δ =−69.9 ppm, which is upfield shifted compared to the solid state CP/MAS 29 Si{ 1 H} NMR chemical shift of bis(NHC)Si(S)S→GaCl 3 complex 34 ( δ =−40.0 ppm) .…”
Section: The Reactivity Of Tetrylonesmentioning
confidence: 99%
“…To synthesize the heavier chalcogenide complexes of tetrylone, the reaction of silylone→GaCl 3 adduct 31 with elemental tellurium has been attempted . However, elemental tellurium does not react with 31 in acetonitrile and the proceeds very slowly in THF.…”
Section: The Reactivity Of Tetrylonesmentioning
confidence: 99%
See 1 more Smart Citation
“…Right:M olecular structure of 4. [14] Ellipsoids are set at 50 %probability;Hatoms are omitted for clarity.S elected interatomic distances []and angles [8 8]: Si1-Te1 2.389(4), Si1-Te2 2.436(2), Si1-C1 1.926(4), Si1-C2 1.944(3);C 2-Si1-C1 90.4(1), Te1-Si-Te2 128.42-(3). [a] NPA charges (q), [b] and Wiberg bond indices (WBI) [b] for compounds 2' ', 3' ' (E = Se), and 4' ' (E = Te).…”
Section: Communicationsmentioning
confidence: 99%
“…Key to these developments have been the usage of suitable synthetic methodologies in combination with thermodynamic and kinetic stabilization by appropriately chosen ligands. In particular, for the heavier carbon analogue silicon, a plethora of studies reported new low-valent compounds in recent years [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] and the chemistry of silylene base adducts has already been carefully developed [14,[26][27][28][29][30][31][32][33][34][35][36]. Before these findings, silyliumylidene ions, cationic Si(II) species were found to be promising as similar versatile Lewis amphiphiles [37,38].…”
Section: Introductionmentioning
confidence: 99%